Hubungan Konsumsi Jajanan dan Status Gizi Anak Sekolah Dasar Negeri 156 Maluku Tengah - Inamah Inamah; Hairudin Rasako; Martha Puspita Sari; Biduri Risna Tuasikal; Khartini Kaluku; Betty A Sahertian; Jacomina Anthonete Salakory (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Elementary school-age children are a group that is vulnerable to nutritional problems. Snacks that do not meet health and nutritional requirements will threaten children's health. The purpose of this study was to determine the relationship between consumption of snacks and nutritional status of children at SD Negeri 156 Central Maluku. The research method used an analytic observational research design with a cross sectional approach. The research location was carried out at 156 Central Maluku Elementary School, Pelauw Village, Haruku Island District, Central Maluku Regency. The research was conducted in February-March 2022. The study population was students of 156 Central Maluku Elementary School grades IV, V, and VI, totaling 62 people. The sample was calculated using the Slovin formula so that 54 people were obtained. The sampling technique uses simple random sampling. Respondents who have frequent snack habits and normal nutritional status > 60%. The results of Chi-square analysis of the relationship between type of snacks, consumption of snacks, and frequency of snacks with children's nutritional status were obtained (p>0.05) which means that there was no relationship between types of snacks, consumption of snacks, and frequency of snacks with children's nutritional status.